Mesoporous silica aerogels for sunflower oil refining and investigation of their adsorption performance - Soylu, Tulay Merve; Ozel, Cem; Ikizler, Burcu Karakuzu; Ozarslan, Ali Can; Terzioglu, Pinar; Elalmis, Yeliz Basaran; Yucel, Sevil (SPRINGER, 2025)
Involving a succession of oil refining stages for edible oil production, a notable constraint lies in the necessity to employ diverse adsorbents at various steps within these processes. This study investigates the synthesis of mesoporous silica aerogels from rice husk ash, comparing their efficacy in physical sunflower oil refining with earth clay (Bentonite) and commercial silica (Trisyl). Tetraethyl orthosilicate (TEOS) impact during aging was analyzed using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and N2 adsorption-desorption analyzer to examine alterations in the structure of silica aerogels. The surface areas of TEOS-doped silica aerogel (TSA) and non-TEOS-doped silica aerogel (NTSA) were 296.18 and 267.06 m(2)/g. Mesoporous silica aerogels were evaluated for their ability to reduce free fatty acids (FFA), peroxide value (PV), phosphorus, and color pigments in sunflower oil. TSA and NTSA demonstrated significant FFA removal, with TSA at 3 wt.% achieving the highest performance of 32.2%. TSA also effectively reduced PV and phosphorus compared to NTSA, Bentonite and Trisyl, exhibiting performance similar to Bentonite in the bleaching process. TEOS-doped silica aerogels have shown promise as adsorbents for impurity removal in sunflower oil and has emerged as the potential adsorbent that can comprehensively and effectively meet the requirements of many edible oil physical refining applications in a singular step. Mesoporous silica aerogel synthesis from rice husk ash with/without TEOS-doping. Mesoporous silica aerogels were compared to commercial adsorbents. For the first time mesoporous silica aerogels were used for oil adsorption with promising results. TEOS-doped silica aerogel was used to remove acids and peroxide in oil purification effectively. TEOS-doped silica aerogel performed effective color and phosphorus removal in oil purification.
Keywords: Bleaching; Oil refining; Rice husk ash; Silica aerogel; Sunflower oil; TEOS; RICE HULL ASH; FATTY-ACIDS; ADSORBENT PERFORMANCE; BLEACHING PERFORMANCE; MASS SPECTROMETRY; LIPID ADSORPTION; PURE SILICA; CANOLA OIL; SOY HULL; PURIFICATION; Materials Science